When Is Torture Right? - McCready, Douglas (Studies in Christian ethics, 2007)
Despite nearly universal condemnation, torture remains a tool for interrogation, intimidation, and punishing. Even many who abhor torture are willing to consider its use in extraordinary situations. Both the deontological absolute prohibition of torture and the consequentialist justification of torture are inadequate ethics to address the issue. Dershowitz, Walzer, and Elshtain, among others, have attempted to redress the problem with more finely-tuned approaches, of which Elshtain's rejection of justification in favor of grace and forgiveness appears the most promising. Confronting the practice of torture is also difficult because there is no generally accepted definition of what constitutes torture. Not all coercion is torture, and some coercion is both legal and moral. Torture, in any case, remains a wrongful act.